Transformasi Digital Marketing untuk UMKM: Studi Kasus Strategi Penjualan Miniatur Kapal Pinisi di Kabupaten Bulukumba - Ilma Wulansari Hasdiansa; Sitti Hasbiah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The impact of the Covid 19 pandemic was also felt by the miniature craftsmen of the phinisi ship in the Bontobahari sub-district, Bulukumba Regency because of marketing limitations that only relied on offline stores. The purpose of this service is to help craftsmen business owners in utilizing digital media as a means of marketing the miniature phinisi boats in the Bontobahari sub-district, Bulukumba Regency. The instruments used in this service are observation, interview and documentation techniques. The results of the service show that there is an increase in the sale of miniature pinisi ships during the use of digital marketing using Instagram and the market reach is also getting wider.